The effect of sintering temperature on the formation of (Tl, Cr)-1212 superconducting ceramic from coprecipitated oxalate precursors - Hamadneh, Imad (Moh'd Khair) Rashid; Lee, Teik Hui; Abd Shukor, Roslan (American Institute of Physics, 2006)
TlSr1212 superconductors were synthesized by solid‐state reaction using Tl‐containing precursor powder prepared by coprecipitation of metal acetates with stoichiometric ratio based on Tl0.85Cr0.15Sr2CaCu2O7−δ composition. The samples were sintered at temperatures between 960 and 980°C for duration of 5 minutes. XRD patterns for samples sintered at 960°C showed formation of dominant 1212 phase in addition to minor 1201 phase and SrCO3 impurity. At this sintering temperature, the best superconducting behavior with TC(R=0) of 100 K was observed for the sample sintered at 970°C. SEM investigations on the sample revealed elongated grains which belong to 1212 phase with a slight directional grain alignment. The sample with sintering temperature of 960°C showed better grains connection as compared to the rest of the samples.